Gambaran Status Gizi Balita Di PUSKESMAS Soriutu - Nuristi Qomalasari; Khoirun Nisa Alfitri; Silvi Lailatul Mahfida (CV. Multi Kreasi Media, 2024)
Background: Suboptimal nutritional status in children under five can lead to more serious health problems. Data from the 2022 Indonesian Nutrition Status Survey (SSGI) revealed that 6.23% of children experience undernutrition. The prevalence of undernutrition in children under five in West Nusa Tenggara (Nusa Tenggara Barat-NTB), according to the 2018 Basic Health Research, is 20.5%, placing NTB second nationally after East Nusa Tenggara (NTT). Objective: This study aims to describe the nutritional status of children under five in the Soriutu Primary Health Center working area. Methodology: This research employed a quantitative approach with an analytical observational design, using a descriptive observational design. The data used in this study were secondary data from the measurement of children under five at the Soriutu Primary Health Center in May 2024. Results: Data analysis of 37 children under five revealed several health issues, including severe stunting (81.1%), severe malnutrition (27%), and significantly low body weight (43.2%). Conclusion: Numerous nutritional issues among children under five were identified in the Soriutu Primary Health Center working area. It is recommended that the local Health Department plan more specific programs to address and reduce undernutrition in NTB.